Sub-nano seconds UWB pulse shaping with reduced ringing phenomenon - Shahid, Zeeshan; Khan, Sheroz; Alam, A. H. M. Zahirul (2012)
In this paper simulation results are obtained, focusing on shaping of a simple sub-nanosecond width UWB pulse generated by a suggested circuit. The shaping is done through using a capacitor-resistor (RC) pair. The RC pair is acting as a high pass filter, allowing the pulse with almost unity gain in the high frequency band. The low frequency components making the width of pulse are difficult to pass, leading to ultimately reducing the pulse width. The pulse from generator circuit is well defined and properly shaped pulse. A capacitor (in the μF range) is connected in series for reducing ringing phenomenon considerably as is shown by the simulation results when compared with what is reported in recent citations. The shape is further enhanced by connecting a low value capacitor in parallel with the load, allowing the high frequency components of the pulse to appear across the load. The pulse shaping circuit is supported by relevant theory, explaining the functioning of the circuit, and to ultimately show how the resulting pulses are related in their widths to parameter values of the circuit elements.